2010
DOI: 10.1016/j.joen.2010.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Markers for Odontogenic Periradicular Periodontitis

Abstract: Introduction The diagnosis and assessment of apical periodontitis by traditional periapical radiographs can be challenging and might yield false-negative results. The aim of this study was to determine whether interleukin-1beta (IL-1β) and dentin sialoprotein (DSP) in gingival crevicular fluid (GCF) can be used as biological markers for apical periodontitis. Methods Forty healthy patients with teeth diagnosed with apical periodontitis of pulpal origin were included in the study. GCF samples were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
2
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
2
17
2
3
Order By: Relevance
“…The results of this study are not in agreement with other studies (35, 36). Siqueira et al (35) reported little to no association with polymorphism and posttreatment apical periodontitis.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study are not in agreement with other studies (35, 36). Siqueira et al (35) reported little to no association with polymorphism and posttreatment apical periodontitis.…”
Section: Discussioncontrasting
confidence: 99%
“…Research works involving the ccomprehension of apical periodontitis mechanisms and the developing of clinical and radiographic signs have emerged in the endodontic literature (39)(40)(41)(42)(43)(44). Morsani et al (41) suggested that the specific genetic markers associated with increased IL-1b production might contribute to apical periodontitis increased susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The increased production of IL-1b has been detected in periapical lesions (6,18), although some researchers have noticed the levels of this cytokine were not statistically different between diseased teeth and healthy control teeth (11,19). In this study when bacterial load of the infected root canal was diminished at day 7, the levels of mRNA expression of IFN-g, IL-1b, and RANKL were significantly decreased (P < .05), whereas the levels of TNF-a and IL-17A mRNA expression were maintained.…”
Section: Discussionmentioning
confidence: 99%